Disentangling the Microphysical Effects of Fire Particles on Convective Clouds Through A Case Study. Issue 12 (16th June 2020) - Takeishi, Azusa; Storelvmo, Trude; Fierce, Laura
Abstract: Aerosol emissions from forest fires may impact cloud droplet activation through an increase in particle number concentrations ("the number effect") and also through a decrease in the hygroscopicity  κ of the entire aerosol population ("the hygroscopicity effect") when fully internal mixing is assumed in models. This study investigated these effects of fire particles on the properties of simulated deep convective clouds (DCCs), using cloud‐resolving simulations with the Weather Research and Forecasting model coupled with Chemistry for a case study in a partly idealized setting. We found that the magnitude of the hygroscopicity effect was in some cases strong enough to entirely offset the number/size effect,  in terms of its influence on modeled droplet and ice crystal concentrations. More specifically, in the case studied here, the droplet number concentration was reduced by about 37% or more due solely to the hygroscopicity effect. In the atmosphere, by contrast, fire particles likely have a much weaker impact on the hygroscopicity of the pre‐existing background aerosol, as such a strong impact would occur only if the fire particles mixed immediately and uniformly with the background. We also show that the differences in the number of activated droplets eventually led to differences in the optical thickness of the clouds aloft, though this finding is limited to only a few hours of the initial development stage of the DCCs. These results suggest that accurately and rigorously representing aerosol mixing and  κ in models is an important step toward accurately simulating aerosol‐cloud interactions under the influence of fires. Key Points: Fire emissions increase aerosol loading and decrease the modeled aerosol hygroscopicity: These have opposite impacts on the simulated clouds The model assumption of fully internal aerosol mixing likely exaggerates the hygroscopicity change due to fire emissions The overestimation of the hygroscopicity effect may lead to underestimation of droplet numbers, especially in fire‐influenced environments